The Clinical Significance and Immunization of MSMO1 in Cervical Squamous Cell Carcinoma Based on Bioinformatics Analysis - Zheng, Guangfei; Wang, Zhuan; Fan, Yuchun; Wang, Tian; Zhang, Linli; Wang, Mengling; Chen, Su; Jiang, Lihe (Frontiers in Genetics, 2021)
Objective The genetic markers for detection or treatment of cervical squamous cell carcinoma (CESC) are not yet complete. The aim of this study was to identify the role of MSMO1 (Alternative name: SC4MOL) in the occurrence and development of CESC. Methods We evaluated the significance of MSMO1 expression in CESC by using analysis of a public dataset from the Cancer Genome Atlas (TCGA) and Gene Expression Omnibus (GEO) database. Oncomine and GEPIA2 were used to validate MSMO1 as an independent prognostic factor in CESC. Multiple tools were used to analyze factors and functions associated with MSMO1, such as methylation, miRNA and co-expressed genes. Furthermore, TIMER and TISIDB were used to study the relationship between MSMO1 expression and immunization in CESC. Results MSMO1 was highly expressed in tumor specimens and could be used as an independent prognostic factor of CESC(p<0.05). But Casiopeinas chemotherapeutics and p63 loss could reduce the expression of MSMO1. The level of methylation MSMO1 was significantly increased in tumor tissues, but insignificant effect on the prognosis. Besides, MSMO1 was closely related to hsa-miR-23a-3p, hsa-miR-23b-3p, hsa-miR-130b-3p and gene IDI1. Specifically, the expression level of MSMO1 had a significant negative correlation with the infiltration level of CD4+T cells, Macrophages, Neutrophils, and DCs in CESC. In addition, GSEA identified differential enrichment in systemic lupus erythematosus, vascular smooth muscle contraction, cytokine receptor interaction, focal adhesion, chemokine signaling pathway, and Leishmania infection pathway in KEGG. Conclusion Our findings provided evidence of MSMO1 implication in tumor, suggesting that MSMO1 is a promising prognostic biomarker in CESC.